The Federal Democratic Republic of Ethiopia : Developing Exports to Promote Growth - World Bank (Washington, DC, 2013)
This report proposes a strategy to promote growth, and poverty reduction through export development. It supports the strategic directions of the Interim Poverty Reduction Strategy Paper (I-PRSP), stressing the importance of improving economic governance, and the environment for investments, for an active participation in the world economy. The report reviews the performance of trade policies, and exports in the 1990s; discusses the new market opportunities; presents the outlook for the international economy; and, proposes a sequenced strategy for launching an export drive that would lead to higher growth. The report's main conclusion is that while the economy has responded well to stabilization measures, and is opening up, it still has a long way to go. Reforms to increase exports must be broad based - that is, extend well beyond trade, and investment liberalization - to include the regulatory framework, the quality of supporting infrastructure, and the overall economic governance.